Triboelectric‐Based Transparent Secret Code. Issue 4 (4th February 2018) - Yuan, Zuqing; Du, Xinyu; Li, Nianwu; Yin, Yingying; Cao, Ran; Zhang, Xiuling; Zhao, Shuyu; Niu, Huidan; Jiang, Tao; Xu, Weihua; Wang, Zhong Lin; Li, Congju
Abstract: Private and security information for personal identification requires an encrypted tool to extend communication channels between human and machine through a convenient and secure method. Here, a triboelectric‐based transparent secret code (TSC) that enables self‐powered sensing and information identification simultaneously in a rapid process method is reported. The transparent and hydrophobic TSC can be conformed to any cambered surface due to its high flexibility, which extends the application scenarios greatly. Independent of the power source, the TSC can induce obvious electric signals only by surface contact. This TSC is velocity‐dependent and capable of achieving a peak voltage of ≈4 V at a resistance load of 10 MΩ and a sliding speed of 0.1 m s −1, according to a 2 mm × 20 mm rectangular stripe. The fabricated TSC can maintain its performance after reciprocating rolling for about 5000 times. The applications of TSC as a self‐powered code device are demonstrated, and the ordered signals can be recognized through the height of the electric peaks, which can be further transferred into specific information by the processing program. The designed TSC has great potential in personal identification, commodity circulation, valuables management, and security defense applications. Abstract : A triboelectric‐based transparent secret code is fabricated to extend channels of communication between human and machine through a convenient and secure method. The self‐powered device communicates with a monitor only by surface contact. However, the device easily compiles the code into specific information in a rapid process according to the reversed program.